Severe Air Pollution and Labor Productivity - Teng Li; Haoming Liu; Alberto Salvo (Institute for the Study of Labor (IZA), 2015)
We examine day-to-day fluctuations in worker-level output over 15 months for a panel of 98 manufacturing workers at a plant located in an industrial city in Hebei province, north China. Long-term workers earn piece-rate wages, with no base pay or minimum pay, for homogeneous tasks performed over fixed 8-hour shifts. Over the sample period, ambient fine-particle (PM2.5) mass concentrations measured at an outdoor air monitor located 2 km from the plant ranged between 10 and 773 micrograms per cubic meter (µg/m3, 8-hour means), variation that is an order of magnitude larger than what is observed in the rich world today. We document large reductions in productivity, of the order of 15%, over the first 200 µg/m3 rise in PM2.5 concentrations, with the drop leveling off for further increases in fine-particle pollution. A back-of-the-envelope calculation suggests that labor productivity across 190 Chinese cities could rise by on average 4% per year were the distributions of hourly PM2.5 truncated at 25 µg/m3. We also find reduced product quality as pollution rises. Our model allows for selection into work attendance, though we do not find particle pollution to be a meaningful determinant of non-attendance, which is very low in our labor setting. Subsequent research should verify the external validity of our findings.
Keywords: J24; Q51; Q52; Q53; O44; R11; 330; PM2.5; labor supply; labor productivity; air pollution; environmental damage